2004
DOI: 10.1128/aem.70.1.224-228.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pathway for Utilization of Cyclopropanecarboxylate by Rhodococcus rhodochrous

Abstract: A new strain isolated from soil utilizes cyclopropanecarboxylate as the sole source of carbon and energy and was identified as Rhodococcus rhodochrous (H. Nishihara, Y. Ochi, H. Nakano, M. Ando, and T. Toraya, J. Ferment. Bioeng. 80:400-402, 1995). A novel pathway for the utilization of cyclopropanecarboxylate, a highly strained compound, by this bacterium was investigated. Cyclopropanecarboxylate-dependent reduction of NAD ؉ in cell extracts of cyclopropanecarboxylate-grown cells was observed. When intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…and the inducible nature of these enzymes ( Blakley, 1978 ). Almost nothing is known about the CPCA metabolic intermediates, while a study on the use of cyclopropanecarboxylate (CPrCA) by R. rhodochrous indicated that CPrCA is initially converted into its CoA thioester which undergoes the ring-opening reaction in order to be further degraded through the β-oxidation pathway ( Toraya et al, 2004 ). In the present study, the chcpca cluster, coding for enzymes involved in β-oxidation reactions, is transcriptionally induced in BCP1 cells utilizing CPCA and CHCA as the only carbon and energy source.…”
Section: Discussionmentioning
confidence: 99%
“…and the inducible nature of these enzymes ( Blakley, 1978 ). Almost nothing is known about the CPCA metabolic intermediates, while a study on the use of cyclopropanecarboxylate (CPrCA) by R. rhodochrous indicated that CPrCA is initially converted into its CoA thioester which undergoes the ring-opening reaction in order to be further degraded through the β-oxidation pathway ( Toraya et al, 2004 ). In the present study, the chcpca cluster, coding for enzymes involved in β-oxidation reactions, is transcriptionally induced in BCP1 cells utilizing CPCA and CHCA as the only carbon and energy source.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sesquiterpene pyridine alkaloids from Tripterygium were predicted to target several proteins and signaling pathways and may play an important role in curing Alzheimer’s disease, Chagas disease, and NAFL ( Long et al, 2021 ). The aminobenzoate degradation pathway could promote tryptophan metabolism and benzoate degradation ( Naidu and Ragsdale, 2001 ; McLeish et al, 2003 ; Toraya et al, 2004 ). The animal studies by Zhang et al showed that the main changes in fecal metabolites of high-fat fed mice included metabolites related to tryptophan metabolism ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis comparing OTA and OTA-Se groups revealed that Nano-Se could influence aminobenzoate and benzoate degradation by elevating 4-Hydroxybenzoic Acid, Protocatechuic Acid levels. This aminobenzoate degradation pathway may promote tryptophan metabolism and benzoate breakdown ( 94 ). Protocatechuic acid, a primary metabolite of complex polyphenols, exhibits numerous biological activities, encompassing antioxidant, anti-inflammatory, antibacterial, and antiapoptotic properties ( 95 97 ).…”
Section: Discussionmentioning
confidence: 99%